Solidarity in the Public Sphere: A Discourse Network Analysis of German Newspapers (2008–2017) - Wallaschek, Stefan (2020)
Multiple crises in the EU have sparked a renaissance of the concept of solidarity. However, discursive approaches to solidarity and the public understanding of solidarity have hardly received scholarly attention. Empirical research on solidarity is rather centered on welfare institutions as well as on individual attitudes and behavior. To shed new light on solidarity in public discourse, we investigate in which policy fields the term is most often used, which actors refer to it and how different types of solidarity are covered in the German public discourse. We investigate the coverage of solidarity in four German newspapers (Die Welt, Frankfurter Allgemeine Zeitung, Süddeutsche Zeitung, Die Tageszeitung) from 2008 to 2017. By deploying the discourse network methodology with 306 claims in 230 news articles, we analyze the co-occurrence of actors and issues over time. Our results indicate a varying set of issues in which solidarity occurs, a rather stable actor visibility, across time and a context-dependent use of different types of solidarity. Government actors, civil society actors as well as citizens drive the solidarity discourse showing that institutional as well as non-institutional actors make use of solidarity in their public actions regarding political protest, financial issues and migration. The study provides novel insights into the interdependence of actor and issue visibility and sheds new light on solidarity in media discourses.